High-Grade Myxoid Liposarcoma (Round Cell Variant) in a Dog. Issue 4 (November 2016) - Plumlee, Q.D.; Hernandez, A.M.; Clark, S.D.; Bascuñán, A.; Davidson, J.; Mansell, J.
Summary: A 10-year-old, neutered male, Basset hound had a 26 × 21 × 21 cm infiltrative mass on the left abdominal wall that did not extend into the peritoneal cavity based on radiographs and abdominal computed tomography. Cytological examination revealed moderate numbers of neoplastic round cells, which frequently contained numerous round, clear, cytoplasmic vacuoles. Histologically, the tumour was composed of two morphologically distinct cell populations forming a continuum of heterogeneously differentiated cells. The primary spindle-shaped population formed streams with abundant, lightly eosinophilic, alcian blue-positive, myxoid matrix. The second population was arranged in sheets and had a round cell appearance. Scattered within both populations were neoplastic cells containing variably sized, intracytoplasmic, osmium tetroxide-positive vacuoles (lipid). Multifocal large pools of mucin formed pseudocysts, and numerous small capillaries were present throughout the neoplasm. According to the current World Health Organization veterinary classification of liposarcomas, this neoplasm had morphological features of both the myxoid and pleomorphic variants of liposarcoma; however, it was analogous to the recently defined high-grade myxoid liposarcoma in man. Myxoid liposarcoma with round cells has not been described previously in dogs. This case highlights the need to potentially re-evaluate the current classification of liposarcomas in animals.